Firm behavior under production uncertainty: Evidence from Russia - Simo Leppänen; Mikael Linden; Laura Solanko (Bank of Finland, Institute for Economies in Transition (BOFIT), 2009)
Enterprises in post-socialist and transition economies often participate in providing infrastructure and social services to the surrounding community. We argue that this bundling of social and infrastructure goods provision with an enterprise s core operations is a fully rational choice in an uncertain environment. Using a stylized model, we show that this activity can be largely related to efforts by firms to increase their operational reliability. Our unique survey data suggest that this manifests itself through provision of more reliable infrastructure, stronger employee attachment to the firm, and better relations with the authorities.
URN:NBN:fi:bof-201408072051
Keywords: 330